Growth, Development and Progress of Islamic Civilization During the Period of Khulafaur Rasyidin - Ahiel Ahdi Besari; Yuyun Ningsih (al-Wadhih: Journal of Islamic History and Civilization, 2025)
The era of the Khulafaur Rasyidin (632–661 CE) marked a crucial initial step in the evolution, progress, and improvement of Islamic civilization that was significant in various dimensions of life. This article analyzes the journey of the transformation of Islamic civilization from a small community in Arabia to a political and civilizational force with a structured system of government, economy, and socio-cultural aspects. Through analytical-descriptive methods and literature studies, this article explains the contributions of each Caliph, Abu Bakr Ash-Shiddiq, ‘Umar bin Khattab, ‘Uthman bin ‘Affan, and ‘Ali bin Abi Thalib in establishing state institutions, regional management, implementing economic and fiscal policies, developing the judicial system, and building social and intellectual infrastructure. The findings of this study indicate that the achievements of the Khulafa Rasyidah were not only seen from their large territorial expansion, but also from their ability to instill Islamic values ​​in governance, develop fair economic management, and encourage intellectual enthusiasm that enabled Islam to emerge as a global civilization. The conclusion of this research reveals that the period of Khulafaur Rasyidin was not only the initial moment of the growth of Islam, but also an important milestone for the exploration and progress of Islamic civilization which had a major influence on human civilization in the future.